Treatment of Ischaemic Stroke - Masuhr, F.; Einhäupl, K. (Thrombosis and Haemostasis, 1999)
Stroke is a neurological emergency that requires rapid diagnostic workup and immediate treatment. Basic medical management such as maintenance of a high level of systemic blood pressure, provision of an optimal supply of oxygen, and correction of hyperthermia, hyperglycaemia and hypovolemia can contribute to a more favourable clinical outcome of stroke patients. Neuroprotective drugs have shown to be effective in reducing cerebral infarct size in several animal species but their clinical benefit in stroke patients remains to be proven. Neither heparin nor aspirin can improve neurological outcome or significantly reduce death or dependency several months after the ischaemic event, but aspirin is clearly effective in reducing early death or stroke recurrence within the first few weeks. Early anticoagulation should be used for patients at high risk for recurrent cardioembolic stroke and with carotid or vertebral artery dissection, although this recommendation is not based on the results of randomised controlled trials.
Keywords: Cerebral ischaemia; general medical management; neuroprotective drugs; heparin; aspirin